Transumbilical laparoscopy-assisted Malone procedure for fecal incontinence in children - Hsuan Huang; Yih-Cherng Duh; Paul Chia-Yu Chang; Yu-Wei Fu; Yao-Jen Hsu; Fu-Huan Huang; Ming-Hung Shen; Chin-Hung Wei (Elsevier, 2022)
Background: Transumbilical laparoscopy-assisted Malone procedure (TULAM) is a single-incision laparoscopic procedure in which the appendicostomy is made at umbilicus. The aim of this study is to evaluate the outcomes of TULAM. Methods: With IRB approval, the medical records of the patients who underwent TULAM were retrospectively reviewed between July 2013 and December 2018. The data collected included ages, gender, underlying diseases, operative techniques, complications, stoma continence, parental satisfaction and follow-up duration. Results: Fifteen patients underwent TULAM at the median age of 5.0 years (2.9-10.7 years). There were 4 girls and 11 boys. Thirteen patients had anorectal malformations or cloaca; the other two patients had spina bifida. All patients presented with fecal incontinence; 9 of them had concomitant constipation. TULAM was successfully accomplished in 14 patients; one patient required conversion to the three-port procedure. The median follow-up period was 1.7 years (0.5-3.2 years). One patient required tube replacement under endoscopy guidance in the operation room. One patient required surgical revision because the appendix was disrupted after an episode of enterocolitis. All patients were socially continent with antegrade enemas. 12 patients were stoma continent, and 3 patients had minor leaking less than once a month. The stoma cosmesis was satisfactory. All parents expressed satisfaction with TULAM. Conclusion: TULAM is effective in the management of fecal incontinence and constipation, and provides a continent stoma with excellent cosmesis.